2017
DOI: 10.22201/fi.25940732e.2017.18n3.024
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the anaerobic digestion of cheese whey in a Plug Flow Reactor (PFR) under local conditions

Abstract: The aim of this study was to analyze the behavior and the stabilization of Cheese Whey (CW) anaerobic digestion in a plug flow reactor by means of the effluent recirculation use and the implementation of the Anaerobic Co-Digestion (ACOD) system with Fresh Dairy Manure (FDM). These alternatives were proposed to avoid the potential acidification. For the monodigestion, it was proved that the system cannot support high OLR. The ACOD of CW with FDM presented a benefic alternative because it implemented a balanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…More recently, phase separation for AD in PFR has been used to digest pineapple pulp [89] and co-digest cheese whey and cow manure [90], which resulted in a removal efficiency of 80.9% COD and 81% VS, correspondingly. Considering these examples, application of PFR as a hydrolysis stage seems feasible and might even offer more advantages by microbial phasing into hydrolysis and acidogenesis stage.…”
Section: High-solid Reactorsmentioning
confidence: 99%
“…More recently, phase separation for AD in PFR has been used to digest pineapple pulp [89] and co-digest cheese whey and cow manure [90], which resulted in a removal efficiency of 80.9% COD and 81% VS, correspondingly. Considering these examples, application of PFR as a hydrolysis stage seems feasible and might even offer more advantages by microbial phasing into hydrolysis and acidogenesis stage.…”
Section: High-solid Reactorsmentioning
confidence: 99%
“…In the research of Carvalho et al (2013), a COD range of 50-102 g•dm −3 was observed [47]. A high variability in LDW was presented in Escalante et al (2017) experiments, where COD ranged between 65 and 140 g•dm −3 [48]. In the Mainardis et al (2019) [49] and Karadag et al (2015) [50] studies, the concentration of COD was 79 g•dm −3 and 60-68.6 g•dm −3 , respectively.…”
Section: Resultsmentioning
confidence: 90%
“…In this regard, anaerobic digestion (AD), a proven technology typically used for the management of different agro-wastes [4,5], can provide a suitable alternative for CW valorisation [6][7][8][9]. However, this waste typically has a low alkalinity and contains a high concentration of organics, all of which makes CW a challenging waste product for AD, usually causing acidification and inhibition of the methanogenic activity [10,11].…”
Section: Introductionmentioning
confidence: 99%